2009
DOI: 10.1074/jbc.m809068200
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Structural Analysis of Bacterial O-antigen Chain Length Regulator Proteins Reveals a Conserved Quaternary Structure

Abstract: Lipopolysaccharide (LPS) is a major component of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
62
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 61 publications
8
62
0
Order By: Relevance
“…Cross-linking analysis with formaldehyde suggests that detergent-solubilized FepE can form dimeric and tetrameric complexes that can assemble into higher molecular mass oligomer forms (Larue et al, 2009). In this study, in situ treatment of FepE and FepE mutants with APDP cross-linker showed that FepE was able to form a number of higher order oligomers (Figs 5 and S2) that did not appear to be larger than 260 kDa (Fig.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Cross-linking analysis with formaldehyde suggests that detergent-solubilized FepE can form dimeric and tetrameric complexes that can assemble into higher molecular mass oligomer forms (Larue et al, 2009). In this study, in situ treatment of FepE and FepE mutants with APDP cross-linker showed that FepE was able to form a number of higher order oligomers (Figs 5 and S2) that did not appear to be larger than 260 kDa (Fig.…”
Section: Discussionmentioning
confidence: 79%
“…Crystallization data on the periplasmic region of FepE and a FepE mutant conferring a shorter LPS Oag chain length show that both form nonamer structures (Kalynych et al, 2012;Tocilj et al, 2008). In contrast, cryo-electron microscopy studies on the full-length FepE reconstituted into proteoliposomes suggest a preference for a hexameric state (Larue et al, 2009).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Cross-linking studies indicate Wzz proteins form homo-oligomers (11), which has been confirmed via several structural analyses (9,12,13). This ability to homo-oligomerize is tied to * This work was supported in part by National Institutes of Health Grants 1 R01 AI068112 and 1 R21 AI53842 (to J.…”
mentioning
confidence: 97%
“…The periplasmic domain structures of a collection of PCP proteins (that also include WzzB SF and WzzB ST ) have been solved (Chang et al, 2015;Kalynych et al, 2012;Larue et al, 2009;Tocilj et al, 2008;Kalynych et al, 2015) and shown that the protomers self-assemble into 3-8 protein oligomers. As Wzz oligomerization has been previously established, the aim of this study is to explore the underlying basis of this interaction.…”
Section: Introductionmentioning
confidence: 99%